Pemertahanan Tradisi Lisan sebagai Identitas Bangsa: Suatu Kajian Tradisi Lisan - Rika Kartika; Ratna Soraya (Keguruan, 2021)
This paper describes the various efforts made to be able to maintain oral traditions, especially the Barus area as a national identity. These efforts include developing studios, storing collections of oral traditions, and the role of the government and the mass media. These efforts are made so that oral traditions are always preserved so that national identity can be recognized by the entire community, both at home and abroad.